Impulse and electric charge characteristics of chemical propellant under pulsed laser irradiation. (October 2021) - Duan, Buren; Zhang, Haonan; Hua, Zuohao; Wu, Lizhi; Bao, Zijing; Guo, Ning; Ye, Yinghua; Shen, Ruiqi
Abstract: To enhance the thrust performance of laser-pulsed plasma thruster (LPPT), we proposed to use chemical propellant as substitute for ordinary PTFE propellant. The discharge characteristics and thrust performance of chemical propellant were analyzed. Meanwhile, the contribution of different energy sources and the physiochemical process between laser and chemical propellant were investigated. The results showed that the chemical propellant had higher plasma peak current and shorter discharge delay time compared to PTFE propellant. For chemical propellant, the contribution of laser energy was about 3%, while the electric energy and chemical energy was less than 17% and more than 80%, respectively. Based on the self-made torsion pendulum micro-impulse test bench, we found the chemical propellant had the highest impulse bit of 27.9 μN·s at 0 V and 69.9 μN·s at 1500 V. Meanwhile, the PTFE propellant had the lowest laser ablation mass, which is 3.70 μg/shot. The chemical reaction between laser and chemical propellant enhances the impulse bit, and increases the mass consumption of the propellant. The chemical propellant had the highest specific impulse, which is 295.1 s at 0 V and 738.5 s at 1500 V. These findings can indicate that the chemical propellant is a better choice than PTFE propellant. Highlights: The technology of electric propulsion and laser propulsion were combined. The chemical propellant was used to replace traditional PTFE propellant. The contribution of different energy sources was analyzed. The physiochemical process between laser and chemical propellant was investigated. The chemical propellant was proven to be the better choice than PTFE propellant.